2012
DOI: 10.1016/j.neuro.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of parkinsonism associated with welding exposure

Abstract: Objective Manganese (Mn), an established neurotoxicant, is a common component of welding fume. The neurological phenotype associated with welding exposures has not been well described. Prior epidemiologic evidence linking occupational welding to parkinsonism is mixed, and remains controversial. Methods This was a cross-sectional and nested case–control study to investigate the prevalence and phenotype of parkinsonism among 811 shipyard and fabrication welders recruited from trade unions. Two reference groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 31 publications
2
144
1
1
Order By: Relevance
“…Our findings fit with others already noted in the scientific literature attesting to the release of manganese from welding activities causing neurologic damage, as well as a variety of other symptoms. This would include the work of Bowler [7], Chandra et al [16], Laohaudomchok et al [8], and Racette et al [9]. The finding in this study proves notable for the high rate of reported eye difficulties, even though most welders wear eye protection, albeit not very consistently.…”
Section: Short-term High Exposures (> 1 Mg/mmentioning
confidence: 48%
See 1 more Smart Citation
“…Our findings fit with others already noted in the scientific literature attesting to the release of manganese from welding activities causing neurologic damage, as well as a variety of other symptoms. This would include the work of Bowler [7], Chandra et al [16], Laohaudomchok et al [8], and Racette et al [9]. The finding in this study proves notable for the high rate of reported eye difficulties, even though most welders wear eye protection, albeit not very consistently.…”
Section: Short-term High Exposures (> 1 Mg/mmentioning
confidence: 48%
“…If one looks at the scientific literature to date, there are differences of opinion as to the ability of manganese in welding rods being capable of causing neurologic damage. Santamaria [6] finds no problem while others [7][8][9] do find RESULTS Out of the 523 questionnaires distributed, 505 were found to be complete and useable. All welders were males of an average age of 33.5±7.6 years old (19-54 years old).…”
Section: Introductionmentioning
confidence: 98%
“…These illnesses include metal fume fever, pneumonitis, pulmonary edema, and lung cancer. Exposure to manganese has been associated with Parkinson-like health effects such as poor hand-eye coordination, motor slowing, increased tremor, reduced response speed, mood disturbance, and possible memory and intellectual loss [Antonini et al 2006;Bowler et al 2006;Lundin et al 2014;Racette et al 2012;Welch et al 2004]. …”
Section: Welding Fumesmentioning
confidence: 99%
“…It should be noted that TCE is the most common organic contaminant in groundwater [ 20 ]. Welding and manganese exposure have been suggested as risk factors for PD [ 21 ]. However, a meta-analysis that pooled data from 13 studies for welding and 3 studies for manganese exposure failed to support this hypothesis [ 22 ].…”
Section: Environmental Factorsmentioning
confidence: 99%